“I Am Afraid of Positioning my Baby in Prone”: Beliefs and Knowledge about Tummy Time Practice - Bianca Fernandes Vasconcelos e Silva; Sabrinne Suelen Santos Sampaio; Julia Raffin Moura; Cléa Emanuela Barreto de Medeiros; Carolina Daniel de Lima-Alvarez; Camila Rocha Simão; Ingrid Guerra Azevedo; Silvana Alves Pereira (International Journal of Pediatrics)
Objective. To identify beliefs and knowledge about tummy time (TT) practice and its repercussions on motor development. Methods. Longitudinal study carried out with parents/caregivers of infants older than 30 days of life. Two assessments were performed. A structured interview was conducted, while the babies were between one and six months old to identify beliefs, knowledge about TT, and the motor milestone achievement expected for the age. At six to 12 months, the risk of motor development delay was tracked using the survey of well-being of young infant questionnaire (SWYC). Results. 41 families responded to the SWYC questionnaire (21 were allocated to the TT group). 31.70% reported that it was not important to put the infants in a prone position while awake, and 70.70% said they are afraid their babies would become breathless when positioned in a prone position. 85.70% of infants from the TT group showed typical development, while 55% of the control group showed atypical development for their age (p=0.01). Only three infants from the control group were at risk of delayed motor development (p=0.10). Conclusions. Most of the families feel insecure about proning their babies and fear breathlessness when positioned. Acquisition of motor milestones prevailed in the TT group, suggesting an association between TT practice and motor milestone achievement.